2000
DOI: 10.1128/iai.68.12.6595-6601.2000
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Adherence Mediated by the Enterotoxigenic Escherichia coli Tia Protein

Abstract: In vitro studies have shown that enterotoxigenic Escherichia coli (ETEC) strains are capable of invading cultured epithelial cells derived from the human ileum and colon. Two separate invasion loci (tia and tib) have previously been isolated from the classical ETEC strain H10407. The tia locus has been shown to direct the synthesis of Tia, a 25-kDa outer membrane protein. Tia is sufficient to confer the adherence and invasion phenotypes on laboratory stains of E. coli, suggesting that this protein is an adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…When added to HCT-8 epithelial cell monolayers immediately prior to inoculation with bacteria, sp.tia76-94 (final concentration, 100 g/ml) reduced invasion of DH5␣(pET185) by 80% Ϯ 3.4%. This peptide is nearly identical to the peptide used in the study of Tia topology of Mammarappallil and Elsinghorst, which showed that this region participates in the Tia-mediated interaction with epithelial cells (36). sp.tia76-94 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When added to HCT-8 epithelial cell monolayers immediately prior to inoculation with bacteria, sp.tia76-94 (final concentration, 100 g/ml) reduced invasion of DH5␣(pET185) by 80% Ϯ 3.4%. This peptide is nearly identical to the peptide used in the study of Tia topology of Mammarappallil and Elsinghorst, which showed that this region participates in the Tia-mediated interaction with epithelial cells (36). sp.tia76-94 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tia and Hek are predicted to have eight transmembrane regions, four long exposed extracellular loops and three short periplasmic turns (Mammarappallil & Elsinghorst, 2000;Fagan et al, 2008). Thus, PagN probably adopts a similar conformation as that of Hek and Tia.…”
Section: Pagn Structurementioning
confidence: 99%
“…subAB 1 ) operon, two new chromosomal variants have been described. The subAB operon is located on the chromosomal pathogenicity island SEPAI, close to the tia gene encoding an invasin in enterotoxigenic E. coli (ETEC) (23,24). The subAB 2-1 genes are about 90% homologous to the plasmid-carried subAB 1 with the catalytic triad being present in subA 2-1 , but the subB 2-1 open reading frame is one triplet shorter than that of subB 1 .…”
mentioning
confidence: 99%